Evaluation of The School Literacy Movement Program at SMP Negeri 2 Serang Baru - Isnaeni, Ari; Baharuddin; Muthi, Ibn (Proceeding International Conference on Education, 2023)
This  study  aims  to  evaluate  the  literacy  program  at  SMPN  2  Serang Baru,  Bekasi  Regency.  This  research  is  evaluative  with  a  descriptive qualitative approach using the CIPP method. The results of the study show1) Context evaluation, including background information, program implementation goals based on needs, and setting up cooperation with related agencies. 2) Evaluation of inputs, such as program development stages, activity schedules, the School Literacy Team, the availability of infrastructure, and program development costs 3) The stages of process evaluation  are  habituation,  development,  and  learning.  Literacy activities are done by teachers, school principals, and other education staff 4) Product evaluation shows the success of the program, namely the  compatibility  of  targets  with  results,  an  increase  in  learning outcomes, and program benefits for schools. In conclusion, this program must  be  continued  with  various  improvements  and  can  be  applied  in other schools.